2020
DOI: 10.3390/cancers12092677
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Tumor Growth, Metastasis, and Signaling Pathways by Reducing FOXM1 Activity in Triple Negative Breast Cancer

Abstract: Metastasis-related complications account for the overwhelming majority of breast cancer mortalities. Triple negative breast cancer (TNBC), the most aggressive breast cancer subtype, has a high propensity to metastasize to distant organs, leading to poor patient survival. The forkhead transcription factor, FOXM1, is especially upregulated and overexpressed in TNBC and is known to regulate multiple signaling pathways that control many key cancer properties, including proliferation, invasiveness, stem cell renewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 41 publications
3
24
0
Order By: Relevance
“…This member of the Forkhead family regulates the expression of a large set of G2/M specific genes, and aberrant FOXM1 upregulation has been shown to be a key driver in cancer progression 26 . Our RNA-seq analysis showed an up-regulation of CDK1 , CDK2 , CDK4 , FoxM1, Aurora A/B , but not of CDK3 , CDK5 , CDK6 , genes in MMTV-R26 Met tumours versus normal mammary glands, as reported in TNBC patients 35 , 36 . Nevertheless, their inhibition together with BCL-XL targeting had no effect on the viability of the four MMTV-R26 Met TNBC cell lines we examined.…”
Section: Discussionsupporting
confidence: 79%
“…This member of the Forkhead family regulates the expression of a large set of G2/M specific genes, and aberrant FOXM1 upregulation has been shown to be a key driver in cancer progression 26 . Our RNA-seq analysis showed an up-regulation of CDK1 , CDK2 , CDK4 , FoxM1, Aurora A/B , but not of CDK3 , CDK5 , CDK6 , genes in MMTV-R26 Met tumours versus normal mammary glands, as reported in TNBC patients 35 , 36 . Nevertheless, their inhibition together with BCL-XL targeting had no effect on the viability of the four MMTV-R26 Met TNBC cell lines we examined.…”
Section: Discussionsupporting
confidence: 79%
“…It is overexpressed in a broad range of cancer types, including breast cancer, ovarian cancer, glioblastoma, pancreatic cancer, prostate cancer, and GI tract cancers [ 3 , 4 , 5 , 6 ]. Its presence is associated with increased cancer cell proliferation and metastasis [ 7 , 8 , 9 , 10 , 11 ]. Hence, there should be therapeutic benefit from inhibiting the activity of FOXM1 in these cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Dose ranges from 0.1 to 10 µM were tested in cells in vitro, and IC50 concentrations for suppression of cell proliferation were 0.7–1 µM for NB73 and NB115 [ 11 ]. Furthermore, both compounds showed good pharmacokinetics and long half-lives in mice after s.c. administration [ 11 ], and they suppressed breast tumor xenograft growth and the expression of tumor FOXM1-regulated genes [ 11 ] and tumor metastasis [ 8 ]. We believe that both inhibition of FOXM1 and reduction in the level of FOXM1 in the cancer cells by these inhibitors contribute to their suppression of FOXM1 activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study by Ziegler et al (153) demonstrated that these novel compounds (including 1,1-diarylethylene mono, diamines, and their corresponding methiodide salts) suppressed FoxM1 activity and breast tumor cell proliferation and growth via cell cycle arrest, and induced apoptosis. Furthermore, Dey et al (154) revealed that the compounds NB-73 and NB-115, through decreasing the expression level of FoxM1 target genes, attenuated the growth, invasiveness, distant metastasis, and the expression of important proteins associated with EMT in TNBC cells.…”
Section: Roles Of Foxm1 In Therapeutics For Breast Cancermentioning
confidence: 99%